P2Y Receptors in Bone - Anabolic, Catabolic, or Both? - Zhou, Yuhan; Arredondo, Hector M.; Wang, Ning (Frontiers in Endocrinology, 2022)
P2Y receptors, including eight subtypes, are G protein-coupled receptors that can be activated by extracellular nucleotides. Nearly all P2Y receptors are expressed in bone cells, suggesting their involvements in bone physiology and pathology. However, their exact roles in bone homeostasis are not entirely clear. Therefore, this mini review summarizes new research developments regarding individual P2Y receptors and their roles in bone biology, particularly detailing those execute both anabolic and catabolic functions. This dual function has highlighted the conundrum of pharmacologically targeting these P2Y receptors in bone-wasting diseases. Further research in finding more precise targeting strategy, such as promoting anabolic effects via combining with physical exercise, should be prioritized.